ANALYSIS OF THE IMPACT OF LEADERSHIP STYLE AND JOB SATISFACTION ON TURNOVER INTENTION THROUGH JOB STRESS AT CUSTOMER SERVICE (FRONTLINE) PT TIKI JALUR NUGRAHA EKAKURIR (JNE) - Sri Mulyani; Hendra Gunawan (Universitas Trisakti, 2017)
The problem of this research was Turnover intention is a factor of discomfort experienced agent in a company. Turnover intention needs to get serious attention to the organization especially to leadership or manager so can applying force leadership proper and improve job satisfaction to reduce job stress in the company.The purpose of this research was the effect of leadership style and job satisfaction toward Turnover intention throught job stress at customer service (frontline) PT Tiki Jalur Nugraha Ekakurir (JNE), Tomang Jakarta.The methodology of this research was testing hypothesis. The data used were primary data collected from questionaire. The samples consisted of 164customer service (frontline)PT Tiki Jalur Nugraha Ekakurir (JNE), which were determined through purposive sampling method. The data were analyzed through Structural Equation Model (SEM) of AMOS version 23.0for Windows.The results of the study showed that there have been negative effect and significant between leadership style and job satisfaction toward Turnover intention throught job stress. The role of job stress very dominant as a mediator the influence of leadership style and job satisfaction toward Turnover intention.Implication of this research is expected to managers can increase the determinants job stress itself for example by raising job satisfaction (salary, reward, job promotion) and applying force leadership proper and able to adjust with all the work situation.